Scalable QoS-based IP multicast over label-switching wireless ATM networks. - Won-Tae Kim (IEEE Network : the magazine of global information exchange)
A Mobile IP multicast prototype that integrates a label-switching wireless asynchronous transfer mode, the mobile core-based multicast architecture, and an Internet multicast infrastructure is presented. MCOM creates multiple core-based layer 2 multicast trees that are independently established in member networks. They are interconnected via the Internet using layer 3 multicast routing. Gateways on the border of the Internet and wireless ATM networks convert ATM multicast traffic to suitable IP packets as well as converting from IP packets to ATM cells for MCOM. To solve the cell interleaving problem that results, ATM block transfer/immediate transmission capability is reasonably modified. Additionally, class-based block buffer management for ATM multicast connections is built into wireless ATM switches for soft quality of service control. Dynamic group management, multicast channel rerouting, and reliable multicasting are also studied in relation to existing Internet protocols like Mobile IP, Internet group management protocols, and multicast routing protocols